Estimation expédiée du risque érosif dans l’amont du bassin versant du Nahr el Kalb - Hussein El Hage Hassan; Laurence Charbel; Ali Khyami (VertigO)
Soil degradation by water erosion is a natural phenomenon that can be amplified by anthropogenic actions. The consequences of this phenomenon are harmful and can harm the intrinsic characteristics of the soil, and lead to its disappearance in certain cases. For mapping the erosion hazard upstream of Nahr el Kalb watershed, we have adopted a hierarchical approach, called MESALES, that combines the weighted parameters of erosion (land use, slope, soil erodibility and climate) using GIS. The soil erodibility was calculated from the equation of Wischmeier et Smith (1960; 1978) to take account of the specific environmental features. The results of this work show the predominant role of plant cover. 67% of the study area is undergoing strong and very strong erosion, mainly in sectors of either degraded plant cover or no plant cover. The overall accuracy of the model and the Kappa index resulting from it are estimated at 84% and 80% respectively